2022
DOI: 10.3390/plants11182396
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Differential Expression Analysis Reveals miRNAs Involved in Dormancy Progression in Sweet Cherry Floral Buds

Abstract: In sweet cherry (Prunus avium), as in other temperate woody perennials, bud dormancy allows for survival in adverse environmental conditions during winter. During this process, environmental signals such as short days and/or low temperatures trigger internal signals that enable buds to become tolerant to the cold. The process involves tracking chilling units up to chilling the requirement fulfillment to resume growth, a transition involving transcriptional regulation, metabolic signaling, and epigenetic-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This difference in results may be due to the different genetic backgrounds of the varieties. In plants such as grape [113], sweet cherry [111], wintersweet [119], and peony [115], miRNAs were found to be involved in regulating the release of dormancy from dormant buds. Recent studies in peach have revealed that several 21-nt sRNAs (small RNAs) and ncRNAs are induced in DAM3 and DAM4 loci, respectively, and this induction was inversely correlated with the down-regulation of homologous DAMs.…”
Section: Species Epigenetic Modification Mechanism Of Gene Expression...mentioning
confidence: 99%
“…This difference in results may be due to the different genetic backgrounds of the varieties. In plants such as grape [113], sweet cherry [111], wintersweet [119], and peony [115], miRNAs were found to be involved in regulating the release of dormancy from dormant buds. Recent studies in peach have revealed that several 21-nt sRNAs (small RNAs) and ncRNAs are induced in DAM3 and DAM4 loci, respectively, and this induction was inversely correlated with the down-regulation of homologous DAMs.…”
Section: Species Epigenetic Modification Mechanism Of Gene Expression...mentioning
confidence: 99%